Chemical and biological warfare a reference handbook - Mauroni, Albert J. 1962- (Contemporary world issues, 2003)
The first introductory work of its kind to survey the fundamentals, policies, and strategies of chemical and biological warfare from 1915 to the present. Virginia-based Mauroni is a senior military analyst with 17 years of experience working on Department of Defense chemical and biological (CB) defense issues. His text provides students and general readers with a concise overview of CB warfare. Coverage includes a history of CB warfare; issues and controversies about CB weapons; reasons why nations develop CB weapons; a chronology of CB warfare; CB weapon systems and defenses against them; organizations, associations, and government and international agencies involved in CB defense and warfare; and an annotated bibliography of print and nonprint resources.